2005
DOI: 10.1191/0269215505cr782oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple sclerosis on respiratory functions

Abstract: Multiple sclerosis clearly impairs respiratory functions; maximal mouth pressures are more severely reduced. This impairment increases with multiple sclerosis-induced disability level but is found to be independent from duration of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 16 publications
6
47
1
8
Order By: Relevance
“…[1][2][3][4] Functional deficits and impairments, such as muscle weakness, fatigue, and impaired ventilation, have long been recognized as major causes of morbidity and mortality in individuals with advanced MS. 5,6 Walking and stair climbing are critically important to maintaining community-level functioning and independence. 7 Tests of lower-extremity function are known to be strong predictors for risk of disability and hospitalization in older community-dwelling persons; [8][9][10][11] however, there are limited data on physical performance function in community-dwelling individuals with MS.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Functional deficits and impairments, such as muscle weakness, fatigue, and impaired ventilation, have long been recognized as major causes of morbidity and mortality in individuals with advanced MS. 5,6 Walking and stair climbing are critically important to maintaining community-level functioning and independence. 7 Tests of lower-extremity function are known to be strong predictors for risk of disability and hospitalization in older community-dwelling persons; [8][9][10][11] however, there are limited data on physical performance function in community-dwelling individuals with MS.…”
Section: Introductionmentioning
confidence: 99%
“…Una musculatura sobre la que se debe prestar especial atención es la musculatura respiratoria, debido a que esta enfermedad se acompaña de una debilidad importante de dicha musculatura, pudiendo ser un mecanismo adicional en el aumento de la discapacidad característica de la enfermedad (177). De este modo, un entrenamiento de 3 sesiones semanales de 30 minutos dirigido al desarrollo de los músculos inspiratorios y espiratorios ha demostrado ser efectivo para mejorar tanto la resistencia a la fatiga de dichos músculos como la puntuación en un cuestionario SF-36-Health Survey, que reflejaría una mejor autopercepción de salud y un menor esfuerzo a la hora de realizar actividades de la vida diaria (178).…”
Section: Entrenamiento Contra Resistencias Y Esclerosis Múltipleunclassified
“…Pulmonary complications and infections are another major cause of morbidity in MS, and their attributable mortality is as much as two-fold higher than in the general population [2]. Pulmonary manifestations of MS consist primarily of respiratory muscle weakness that leads to impaired ventilation and poor cough [1, [3][4][5][6]. Several reports have suggested that the expiratory muscles are preferentially involved [1,3].…”
mentioning
confidence: 99%
“…Children are not usually included in global surveys of MDR-TB incidence and prevalence [2] due to the diagnostic challenges of paucibacillary TB [3]. Data on the burden of MDR-TB in children are, therefore, lacking globally [1, 4,5] and no published data from the UK exist. The current World Health Organization (WHO) [6] and National Institute for Clinical Excellence (NICE) [7] TB guidelines for the management of MDR-TB do not explicitly address paediatric disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation